/- Copyright (c) 2014 Parikshit Khanna. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Module: data.list.basic Authors: Parikshit Khanna, Jeremy Avigad, Leonardo de Moura Basic properties of lists. -/ import logic tools.helper_tactics data.nat.basic open eq.ops helper_tactics nat prod function inductive list (T : Type) : Type := | nil {} : list T | cons : T → list T → list T namespace list notation h :: t := cons h t notation `[` l:(foldr `,` (h t, cons h t) nil `]`) := l variable {T : Type} /- append -/ definition append : list T → list T → list T | [] l := l | (h :: s) t := h :: (append s t) notation l₁ ++ l₂ := append l₁ l₂ theorem append_nil_left (t : list T) : [] ++ t = t theorem append_cons (x : T) (s t : list T) : (x::s) ++ t = x::(s ++ t) theorem append_nil_right : ∀ (t : list T), t ++ [] = t | [] := rfl | (a :: l) := calc (a :: l) ++ [] = a :: (l ++ []) : rfl ... = a :: l : append_nil_right l theorem append.assoc : ∀ (s t u : list T), s ++ t ++ u = s ++ (t ++ u) | [] t u := rfl | (a :: l) t u := show a :: (l ++ t ++ u) = (a :: l) ++ (t ++ u), by rewrite (append.assoc l t u) /- length -/ definition length : list T → nat | [] := 0 | (a :: l) := length l + 1 theorem length_nil : length (@nil T) = 0 theorem length_cons (x : T) (t : list T) : length (x::t) = length t + 1 theorem length_append : ∀ (s t : list T), length (s ++ t) = length s + length t | [] t := calc length ([] ++ t) = length t : rfl ... = length [] + length t : zero_add | (a :: s) t := calc length (a :: s ++ t) = length (s ++ t) + 1 : rfl ... = length s + length t + 1 : length_append ... = (length s + 1) + length t : add.succ_left ... = length (a :: s) + length t : rfl -- add_rewrite length_nil length_cons /- concat -/ definition concat : Π (x : T), list T → list T | a [] := [a] | a (b :: l) := b :: concat a l theorem concat_nil (x : T) : concat x [] = [x] theorem concat_cons (x y : T) (l : list T) : concat x (y::l) = y::(concat x l) theorem concat_eq_append (a : T) : ∀ (l : list T), concat a l = l ++ [a] | [] := rfl | (b :: l) := show b :: (concat a l) = (b :: l) ++ (a :: []), by rewrite concat_eq_append -- add_rewrite append_nil append_cons /- reverse -/ definition reverse : list T → list T | [] := [] | (a :: l) := concat a (reverse l) theorem reverse_nil : reverse (@nil T) = [] theorem reverse_cons (x : T) (l : list T) : reverse (x::l) = concat x (reverse l) theorem reverse_singleton (x : T) : reverse [x] = [x] theorem reverse_append : ∀ (s t : list T), reverse (s ++ t) = (reverse t) ++ (reverse s) | [] t2 := calc reverse ([] ++ t2) = reverse t2 : rfl ... = (reverse t2) ++ [] : append_nil_right ... = (reverse t2) ++ (reverse []) : by rewrite reverse_nil | (a2 :: s2) t2 := calc reverse ((a2 :: s2) ++ t2) = concat a2 (reverse (s2 ++ t2)) : rfl ... = concat a2 (reverse t2 ++ reverse s2) : reverse_append ... = (reverse t2 ++ reverse s2) ++ [a2] : concat_eq_append ... = reverse t2 ++ (reverse s2 ++ [a2]) : append.assoc ... = reverse t2 ++ concat a2 (reverse s2) : concat_eq_append ... = reverse t2 ++ reverse (a2 :: s2) : rfl theorem reverse_reverse : ∀ (l : list T), reverse (reverse l) = l | [] := rfl | (a :: l) := calc reverse (reverse (a :: l)) = reverse (concat a (reverse l)) : rfl ... = reverse (reverse l ++ [a]) : concat_eq_append ... = reverse [a] ++ reverse (reverse l) : reverse_append ... = reverse [a] ++ l : reverse_reverse ... = a :: l : rfl theorem concat_eq_reverse_cons (x : T) (l : list T) : concat x l = reverse (x :: reverse l) := calc concat x l = concat x (reverse (reverse l)) : reverse_reverse ... = reverse (x :: reverse l) : rfl /- head and tail -/ definition head [h : inhabited T] : list T → T | [] := arbitrary T | (a :: l) := a theorem head_cons [h : inhabited T] (a : T) (l : list T) : head (a::l) = a theorem head_append [h : inhabited T] (t : list T) : ∀ {s : list T}, s ≠ [] → head (s ++ t) = head s | [] H := absurd rfl H | (a :: s) H := show head (a :: (s ++ t)) = head (a :: s), by rewrite head_cons definition tail : list T → list T | [] := [] | (a :: l) := l theorem tail_nil : tail (@nil T) = [] theorem tail_cons (a : T) (l : list T) : tail (a::l) = l theorem cons_head_tail [h : inhabited T] {l : list T} : l ≠ [] → (head l)::(tail l) = l := list.cases_on l (assume H : [] ≠ [], absurd rfl H) (take x l, assume H : x::l ≠ [], rfl) /- list membership -/ definition mem : T → list T → Prop | a [] := false | a (b :: l) := a = b ∨ mem a l notation e ∈ s := mem e s theorem mem_nil (x : T) : x ∈ [] ↔ false := iff.rfl theorem mem_cons (x y : T) (l : list T) : x ∈ y::l ↔ (x = y ∨ x ∈ l) := iff.rfl theorem mem_or_mem_of_mem_append {x : T} {s t : list T} : x ∈ s ++ t → x ∈ s ∨ x ∈ t := list.induction_on s or.inr (take y s, assume IH : x ∈ s ++ t → x ∈ s ∨ x ∈ t, assume H1 : x ∈ y::s ++ t, have H2 : x = y ∨ x ∈ s ++ t, from H1, have H3 : x = y ∨ x ∈ s ∨ x ∈ t, from or_of_or_of_imp_right H2 IH, iff.elim_right or.assoc H3) theorem mem_append_of_mem_or_mem {x : T} {s t : list T} : x ∈ s ∨ x ∈ t → x ∈ s ++ t := list.induction_on s (take H, or.elim H false.elim (assume H, H)) (take y s, assume IH : x ∈ s ∨ x ∈ t → x ∈ s ++ t, assume H : x ∈ y::s ∨ x ∈ t, or.elim H (assume H1, or.elim H1 (take H2 : x = y, or.inl H2) (take H2 : x ∈ s, or.inr (IH (or.inl H2)))) (assume H1 : x ∈ t, or.inr (IH (or.inr H1)))) theorem mem_append_iff (x : T) (s t : list T) : x ∈ s ++ t ↔ x ∈ s ∨ x ∈ t := iff.intro mem_or_mem_of_mem_append mem_append_of_mem_or_mem local attribute mem [reducible] local attribute append [reducible] theorem mem_split {x : T} {l : list T} : x ∈ l → ∃s t : list T, l = s ++ (x::t) := list.induction_on l (take H : x ∈ [], false.elim (iff.elim_left !mem_nil H)) (take y l, assume IH : x ∈ l → ∃s t : list T, l = s ++ (x::t), assume H : x ∈ y::l, or.elim H (assume H1 : x = y, exists.intro [] (!exists.intro (H1 ▸ rfl))) (assume H1 : x ∈ l, obtain s (H2 : ∃t : list T, l = s ++ (x::t)), from IH H1, obtain t (H3 : l = s ++ (x::t)), from H2, have H4 : y :: l = (y::s) ++ (x::t), from H3 ▸ rfl, !exists.intro (!exists.intro H4))) definition decidable_mem [instance] [H : decidable_eq T] (x : T) (l : list T) : decidable (x ∈ l) := list.rec_on l (decidable.inr (not_of_iff_false !mem_nil)) (take (h : T) (l : list T) (iH : decidable (x ∈ l)), show decidable (x ∈ h::l), from decidable.rec_on iH (assume Hp : x ∈ l, decidable.rec_on (H x h) (assume Heq : x = h, decidable.inl (or.inl Heq)) (assume Hne : x ≠ h, decidable.inl (or.inr Hp))) (assume Hn : ¬x ∈ l, decidable.rec_on (H x h) (assume Heq : x = h, decidable.inl (or.inl Heq)) (assume Hne : x ≠ h, have H1 : ¬(x = h ∨ x ∈ l), from assume H2 : x = h ∨ x ∈ l, or.elim H2 (assume Heq, absurd Heq Hne) (assume Hp, absurd Hp Hn), have H2 : ¬x ∈ h::l, from iff.elim_right (not_iff_not_of_iff !mem_cons) H1, decidable.inr H2))) /- find -/ section variable [H : decidable_eq T] include H definition find : T → list T → nat | a [] := 0 | a (b :: l) := if a = b then 0 else succ (find a l) theorem find_nil (x : T) : find x [] = 0 theorem find_cons (x y : T) (l : list T) : find x (y::l) = if x = y then 0 else succ (find x l) theorem find.not_mem {l : list T} {x : T} : ¬x ∈ l → find x l = length l := list.rec_on l (assume P₁ : ¬x ∈ [], _) (take y l, assume iH : ¬x ∈ l → find x l = length l, assume P₁ : ¬x ∈ y::l, have P₂ : ¬(x = y ∨ x ∈ l), from iff.elim_right (not_iff_not_of_iff !mem_cons) P₁, have P₃ : ¬x = y ∧ ¬x ∈ l, from (iff.elim_left not_or_iff_not_and_not P₂), calc find x (y::l) = if x = y then 0 else succ (find x l) : !find_cons ... = succ (find x l) : if_neg (and.elim_left P₃) ... = succ (length l) : {iH (and.elim_right P₃)} ... = length (y::l) : !length_cons⁻¹) end /- nth element -/ definition nth [h : inhabited T] : list T → nat → T | [] n := arbitrary T | (a :: l) 0 := a | (a :: l) (n+1) := nth l n theorem nth_zero [h : inhabited T] (a : T) (l : list T) : nth (a :: l) 0 = a theorem nth_succ [h : inhabited T] (a : T) (l : list T) (n : nat) : nth (a::l) (n+1) = nth l n open decidable definition decidable_eq {A : Type} [H : decidable_eq A] : ∀ l₁ l₂ : list A, decidable (l₁ = l₂) | [] [] := inl rfl | [] (b::l₂) := inr (λ H, list.no_confusion H) | (a::l₁) [] := inr (λ H, list.no_confusion H) | (a::l₁) (b::l₂) := match H a b with | inl Hab := match decidable_eq l₁ l₂ with | inl He := inl (eq.rec_on Hab (eq.rec_on He rfl)) | inr Hn := inr (λ H, list.no_confusion H (λ Hab Ht, absurd Ht Hn)) end | inr Hnab := inr (λ H, list.no_confusion H (λ Hab Ht, absurd Hab Hnab)) end section combinators variables {A B C : Type} definition map (f : A → B) : list A → list B | [] := [] | (a :: l) := f a :: map l theorem map_nil (f : A → B) : map f [] = [] theorem map_cons (f : A → B) (a : A) (l : list A) : map f (a :: l) = f a :: map f l theorem map_map (g : B → C) (f : A → B) : ∀ l : list A, map g (map f l) = map (g ∘ f) l | [] := rfl | (a :: l) := show (g ∘ f) a :: map g (map f l) = map (g ∘ f) (a :: l), by rewrite (map_map l) theorem len_map (f : A → B) : ∀ l : list A, length (map f l) = length l | [] := rfl | (a :: l) := show length (map f l) + 1 = length l + 1, by rewrite (len_map l) definition map₂ (f : A → B → C) : list A → list B → list C | [] _ := [] | _ [] := [] | (x::xs) (y::ys) := f x y :: map₂ xs ys definition foldl (f : A → B → A) : A → list B → A | a [] := a | a (b :: l) := foldl (f a b) l definition foldr (f : A → B → B) : B → list A → B | b [] := b | b (a :: l) := f a (foldr b l) section foldl_eq_foldr -- foldl and foldr coincide when f is commutative and associative parameters {α : Type} {f : α → α → α} hypothesis (Hcomm : ∀ a b, f a b = f b a) hypothesis (Hassoc : ∀ a b c, f a (f b c) = f (f a b) c) include Hcomm Hassoc theorem foldl_eq_of_comm_of_assoc : ∀ a b l, foldl f a (b::l) = f b (foldl f a l) | a b nil := Hcomm a b | a b (c::l) := begin change (foldl f (f (f a b) c) l = f b (foldl f (f a c) l)), rewrite -foldl_eq_of_comm_of_assoc, change (foldl f (f (f a b) c) l = foldl f (f (f a c) b) l), have H₁ : f (f a b) c = f (f a c) b, by rewrite [-Hassoc, -Hassoc, Hcomm b c], rewrite H₁ end theorem foldl_eq_foldr : ∀ a l, foldl f a l = foldr f a l | a nil := rfl | a (b :: l) := begin rewrite foldl_eq_of_comm_of_assoc, esimp, change (f b (foldl f a l) = f b (foldr f a l)), rewrite foldl_eq_foldr end end foldl_eq_foldr definition all (p : A → Prop) (l : list A) : Prop := foldr (λ a r, p a ∧ r) true l definition any (p : A → Prop) (l : list A) : Prop := foldr (λ a r, p a ∨ r) false l definition decidable_all (p : A → Prop) [H : decidable_pred p] : ∀ l, decidable (all p l) | [] := decidable_true | (a :: l) := match H a with | inl Hp₁ := match decidable_all l with | inl Hp₂ := inl (and.intro Hp₁ Hp₂) | inr Hn₂ := inr (not_and_of_not_right (p a) Hn₂) end | inr Hn := inr (not_and_of_not_left (all p l) Hn) end definition decidable_any (p : A → Prop) [H : decidable_pred p] : ∀ l, decidable (any p l) | [] := decidable_false | (a :: l) := match H a with | inl Hp := inl (or.inl Hp) | inr Hn₁ := match decidable_any l with | inl Hp₂ := inl (or.inr Hp₂) | inr Hn₂ := inr (not_or Hn₁ Hn₂) end end definition zip (l₁ : list A) (l₂ : list B) : list (A × B) := map₂ (λ a b, (a, b)) l₁ l₂ definition unzip : list (A × B) → list A × list B | [] := ([], []) | ((a, b) :: l) := match unzip l with | (la, lb) := (a :: la, b :: lb) end theorem unzip_nil : unzip (@nil (A × B)) = ([], []) theorem unzip_cons (a : A) (b : B) (l : list (A × B)) : unzip ((a, b) :: l) = match unzip l with (la, lb) := (a :: la, b :: lb) end theorem zip_unzip : ∀ (l : list (A × B)), zip (pr₁ (unzip l)) (pr₂ (unzip l)) = l | [] := rfl | ((a, b) :: l) := begin rewrite unzip_cons, have r : zip (pr₁ (unzip l)) (pr₂ (unzip l)) = l, from zip_unzip l, revert r, apply (prod.cases_on (unzip l)), intros (la, lb, r), rewrite -r end end combinators /- flat -/ variable {A : Type} definition flat (l : list (list A)) : list A := foldl append nil l end list attribute list.decidable_eq [instance] attribute list.decidable_mem [instance] attribute list.decidable_any [instance] attribute list.decidable_all [instance]